Investigation of tensile deformation behavior of a TWIP/TRIP metastable β titanium alloy at typical temperature part Ⅱ: 20 K - Y.B. Zhang; S.W. Xin; T. Li; G.J. Zhang; B.K. Zhao (Materials & Design)
The tensile behavior and deformation mechanism of Ti-10Mo alloy at liquid hydrogen temperature (20 K) were investigated. The results showed that Ti-10Mo alloy has a high UTS of 1553 MPa and a high YS of 1497 MPa at 20 K, as well as an excellent elongation after fracture of 11 %. This is due to the simultaneous activation of {332}<113> twin twins and SIM α“ transformation during deformation, that is, the combination of TWIP and TRIP effects. The activation sequence of different deformation mechanisms is as follows: the primary SIM α” and {332}<113> twins are first activated simultaneously. With the increase of strain, multiple variants of SIM α“ and {332}<113> twins can be activated in a grain. Then the primary SIM α” can be further transformed into {130}<310>α“ twins. With the further increase of strain, some {130}<310>α” twins can continue to be transformed into secondary {332}<113>β twin and some primary {332}<113> twins can also produce secondary α“ to continue the deformation. When necking, a large number of {111}α” twins are activated to further coordinate the plastic deformation. In addition, the multiple necking phenomenon is due to the further activation of {332}<113> twins and SIM α“ during the necking of a certain area due to stress concentration during the stretching process, which causes local strengthening and resulting in the stop of necking. Finally, the serrations on the stress–strain curve may be caused by multiple necking.